Andragogy in Practice: Applying a Theoretical Framework to Team Science Training in Biomedical Research - Jacqueline M. Knapke; Laura Hildreth; Jennifer R. Molano; Stephanie M. Schuckman; Jason T. Blackard; Megan Johnstone; Elizabeth J. Kopras; M. K. Lamkin; M. K. Lamkin; Rebecca C. Lee; John R. Kues; Angela Mendell (Frontiers Media S.A., 2024)
This study is the first to apply the theoretical principles of Malcolm Knowles' theory of andragogy to evaluate data collected from learners who participated in team science training workshops in a biomedical research setting. Briefly, andragogy includes six principles: the learner's self-concept, the role of experience, readiness to learn, orientation to learning, the learner's need to know, and intrinsic motivation. Using an embedded study design, the primary focus was on qualitative data, with quantitative data complementing the qualitative findings. The deductive analysis demonstrated that approximately 85% of the qualitative data could be connected to at least one andragogical principle. Participant responses to positive evaluation questions were largely related to two principles: readiness to learn and problem-based learning orientation. Participant responses to negative questions were largely connected to two different principles: the role of experience and self-direction. Inductive analysis found an additional theme: meeting biological needs. Quantitative survey results supported the qualitative findings. The study findings demonstrate that andragogy can serve as a valuable construct to integrate into the development of effective team science training for biomedical researchers.